Design and Implementation of Management Information System for Senior High School Student Dormitory for Lokon Santo Nikolaus Tomohon - Kho, Erik Erlando; Najoan, Xaverius B.N.; Jacobus, Agustinus (Universitas Sam Ratulangi, 2021)
Abstract â€” To be able to propose and develop an organization, a management information system is needed, because the management information system can process data accurately, so that the information obtained can be arranged in a practical and systematic manner and can also support the smooth running of activities and daily organizational activities. Lokon St. High School Nikolaus Tomohon is one of the boarding educational institutions, which still requires a management information system to support the activities and activities in it. Because the student data collection process in the dormitory is manual and requires an accurate and fast management information system so that the data collection process can run efficiently. With the existing problems, a hostel management information system application was built that could support the student information data collection process at Lokon St. High School. Nikolaus Tomohon, who was previously manual, became systematic in order to be more optimal, accurate and fast. The system development method used in this research is the waterfall method.Keyword: Application Design; Implementation; Management information System.Â Abstrakâ€” Untuk dapat memajukan dan mengembangkan suatu organisasi diperlukan adanya sistem informasi manajemen, karena sistem informasi manajemen dapat mengolah data dengan akurat, sehingga informasi yang diperoleh dapat tersusun secara praktis dan sistematis dan juga dapat menunjang kelancaran aktivitas dan kegiatan organisasi sehari-hari. SMA Lokon St. Nikolaus Tomohon merupakan salah satu lembaga pendidikan berasrama, yang masih memerlukan sistem informasi manajemen untuk menunjang aktivitas dan kegiatan yang ada didalamnya. Karena proses pendataan siswa di dalam asrama masih bersifat manual dan memerlukan adanya sistem informasi manjemen yang akurat dan cepat sehingga proses pendataan dapat berjalan dengan efisien. Dengan permasalahan yang ada maka dibangun aplikasi sistem informasi manajemen asrama yang dapat menunjang proses pendataan informasi siswa di SMA Lokon St. Nikolaus Tomohon yang sebelumnya masih bersifat manual menjadi sistematis agar lebih optimal, akurat dan cepat. Metode pengembangan sistem yang digunakan dalam penelitian ini adalah metode waterfall. Kata Kunci: Implementasi; Perancangan Aplikasi; Sistem Informasi Manajemen.